Cauchy problem for parabolic systems with pulse action - Luchko, V. M.; Matychuk, M. I. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
For linear parabolic systems with pulse action, we establish the well-posedness of the Cauchy problem in normed Dini spaces.